The Central Role of Glia in Pathological Pain and the Potential of Targeting the Cannabinoid 2 Receptor for Pain Relief - Wilkerson, Jenny L. (2011)
Under normal conditions, acute pain processing consists of well-characterized neuronal signaling events. When dysfunctional pain signaling occurs, pathological pain ensues. Glial activation and their released factors participate in the mediation of pathological pain. The use of cannabinoid compounds for pain relief is currently an area of great interest for both basic scientists and physicians. These compounds, bind mainly either the cannabinoid receptor subtype 1 (CB(1)R) or cannabinoid receptor subtype 2 (CB(2)R) and are able to modulate pain. Although cannabinoids were initially only thought to modulate pain via neuronal mechanisms within the central nervous system, strong evidence now supports that CB(2)R cannabinoid compounds are capable of modulating glia, (e.g. astrocytes and microglia) for pain relief. However, the mechanisms underlying cannabinoid receptor-mediated pain relief remain largely unknown. An emerging body of evidence supports that CB(2)R agonist compounds may prove to be powerful novel therapeutic candidates for the treatment of chronic pain.